Shanghai fever, a fatal enteric illness, in an adult patient with neutropenia caused by treatment-related myelodysplastic syndrome: a case report - Taichi Horino; Tatsunori Miyata; Mitsuhiro Inoue; Kosuke Ono; Asuka Ono; Yoshiyuki Tagayasu; Daichi Nomoto; Takao Mizumoto; Tatsuo Kubota; Nobutomo Miyanari; Hideo Baba (Surgical Case Reports)
Abstract Background Shanghai fever is a rare community-acquired enteric illness with sepsis caused by Pseudomonas aeruginosa. Cases of Shanghai fever in pediatric patients have been reported; however, to the best of our knowledge, there are no reports of adult cases. Case presentation A 65-year-old man visited the emergency department with sudden onset of abdominal pain. He was diagnosed as treatment-related myelodysplastic syndrome after treatment of follicular lymphoma. Moderate tenderness in the middle right abdominal quadrants was noted. Computed tomography showed abdominal free air with a small amount of effusion to the surrounding edematous small intestine, and we performed emergency exploration. During operation, we found multiple bowel perforations with patchy necrotic lesions. The patient was admitted to an intensive care unit postoperatively. Blood culture showed Pseudomonas aeruginosa. His condition improved; however, on the 8th postoperative day, the abdominal drain tube showed turbid drainage. We performed re-operation and found anastomotic leakage with two new bowel perforations. After the re-operation, the patient showed signs of septic shock and his general condition got worse, and the patient died due to multiple organ failure on the 12th postoperative day. Conclusion Shanghai fever may occur in an adult patient with neutropenia.